Antibiotherapy in Children with Cystic Fibrosis-An Extensive Review - Ioana Mihaiela Ciuca; Mihaela Dediu; Diana Popin; Liviu Laurentiu Pop; Liviu Athos Tamas; Ciprian Nicolae Pilut; Bogdan Almajan Guta; Zoran Laurentiu Popa (MDPI AG, 2022)
In cystic fibrosis (CF), the respiratory disease is the main factor that influences the outcome and the prognosis of patients, bacterial infections being responsible for severe exacerbations. The etiology is often multi-microbial and with resistant strains. The aim of this paper is to present current existing antibiotherapy solutions for CF-associated infections in order to offer a reliable support for individual, targeted, and specific treatment. The inclusion criteria were studies about antibiotherapy in CF pediatric patients. Studies involving adult patients or those with only in vitro results were excluded. The information sources were all articles published until December 2021, in PubMed and ScienceDirect. A total of 74 studies were included, with a total number of 26,979 patients aged between 0-18 years. We approached each pathogen individual, with their specific treatment, comparing treatment solutions proposed by different studies. Preservation of lung function is the main goal of therapy in CF, because once parenchyma is lost, it cannot be recovered. Early personalized intervention and prevention of infection with reputable germs is of paramount importance, even if is an asymmetrical challenge. This research received no external funding.